Stereotype threat. [article]. - Spencer, Steven J.
When members of a stigmatized group find themselves in a situation where negative stereotypes provide a possible framework for interpreting their behavior, the risk of being judged in light of those stereotypes can elicit a disruptive state that undermines performance and aspirations in that domain. This situational predicament, termed stereotype threat, continues to be an intensely debated and researched topic in educational, social, and organizational psychology. In this review, we explore the various sources of stereotype threat, the mechanisms underlying stereotype effects (both mediators and moderators), and the consequences of this situational predicament, as well as the means through which society and stigmatized individuals can overcome the insidious effects of stereotype threat. ultimately, we hope this review alleviates some of the confusion surrounding stereotype threat while also sparking further research and debate. -- (from the authors)
Keywords: Logel, Christine; Davies, Paul; Stereotype threat; Social identity; Identify safety; Stereotypes; Prejudice; Discrimination